2014
DOI: 10.1016/j.trsl.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

New tides: using zebrafish to study renal regeneration

Abstract: Over the past several decades, the zebrafish has become one of the major vertebrate model organisms used in biomedical research. In this arena, the zebrafish has emerged as an applicable system for the study of kidney diseases and renal regeneration. The relevance of the zebrafish model for nephrology research has been increasingly appreciated as the understanding of zebrafish kidney structure, ontogeny, and the response to damage has steadily expanded. Recent studies have documented the amazing regenerative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 87 publications
4
62
0
Order By: Relevance
“…For clcn2b, we could observe at 26-h postfertilization (hpf) staining in the pronephros of the embryo (Fig. 4a-c), in a region corresponding to the proximal convoluted tubule [37]. We performed a double staining with clcnk, expressed in the distal tubule [55], confirming the identity of the pronephric segment where clcn2b is expressed.…”
Section: Whole Embryo In Situ Hybridization Analysissupporting
confidence: 57%
“…For clcn2b, we could observe at 26-h postfertilization (hpf) staining in the pronephros of the embryo (Fig. 4a-c), in a region corresponding to the proximal convoluted tubule [37]. We performed a double staining with clcnk, expressed in the distal tubule [55], confirming the identity of the pronephric segment where clcn2b is expressed.…”
Section: Whole Embryo In Situ Hybridization Analysissupporting
confidence: 57%
“…Lotus tetragonolobus lectin (LTL) (proximal tubules marker) and Dolichos biflorus agglutinin (DBA; distal tubules and collective ducts marker) were used as markers of nephron segments. 19,20 Kim-1 was expressed on the apical membrane of proximal tubular cells but not distal tubular or collecting duct cells after gentamicin-induced kidney injury ( Figure 3A). The timecourse of expression of kim1 mRNA revealed that kim1-L and kim1-S transcripts in adult zebrafish kidney were upregulated by 2 days postgentamicin injection (dpi), and remained elevated until 8 dpi, after which they decreased to near-normal levels at 12 dpi, while the expression of kim1-Ig or kim3 and kim4 transcripts was not altered by gentamicin administration ( Figure 3B).…”
Section: Identification Of Zebrafish Kim-1 Familymentioning
confidence: 99%
“…Specifically, it would aid in renal developmental studies, to investigate how different molecules affect nephron segmentation 42 and tubulogenesis 43,44 , processes that are only superficially understood at present. Furthermore, microbead implantation has begun to be used to study regeneration processes in zebrafish 29] and could be adapted for use with any number of organ regeneration models, such as following laser ablation of embryonic tissues like the nephron 45 or in conjunction with methods that have been formulated to perform research with the corresponding adult structures [46][47][48][49] . Finally, microbead implantation has the potential to be used in models of human disease, such as cancer 50,51 or tissue degeneration 52,53 .…”
Section: Discussionmentioning
confidence: 99%